Philippine Muslim youths in Iloilo City their personal well-being, sense of national identity, and views on post 9/11 sociopolitical issues. - Balalilhe, Charinson; Guillerme, Kerry Anne.
This research examined the personal well-being, sense of national identity, and views on post 9/11 sociopolitical issues of Philippine Muslim youths in Iloilo City., Twenty-one (21) males and twelve (12) females, 13-27 years of age, unmarried and of Maranao descent participated in this research. Scales were used to rate the respondents' personal well-being and for general ethnicity. A questionnaire for pride in being Filipino used to determine their sense of national identity, and an open-ended questionnaire to determine their views on post 9/11 sociopolitical issues. It was found out that the Philippine Muslim youths in Iloilo City have high level personal well-being where most respondents showed high scores in self-esteem, self-efficacy, and satisfaction with life. Most of the respondents also showed strong national identity. Respondents had held different views on post 0/11 sociopolitical issues. While 76 percent do not support the terrorists group, others (45 percent) do not support the man-hunt against it, and that 48 percent believe that the 9/11 event was plain terrorism.
Thesis (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Muslims -- Youth -- Iloilo City